Study of the Relationship between Intercultural Sensitivity and Intercultural Communication Competence among International Postgraduate Students: A Case Study at University Malaysia Pahang - Sarwari, Abdul Qahar; Muhammad Nubli, Abdul Wahab (Taylor & Francis, 2017)
This study assessed the relationship between intercultural sensitivity and intercultural communication competence among international postgraduate students at University Malaysia Pahang. The two mentioned concepts are among the key factors that enable people to conduct proper intercultural interactions. The study includes the quantitative and the interview datasets, and the participants of this study were 108 international postgraduate students from 17 different countries. The outcomes from the current study illustrate that intercultural sensitivity and intercultural communication competence are the main factors that help individuals to conduct proper and effective intercultural communication with people from different cultures. Based on the results, intercultural sensitivity and intercultural communication competence have close relationships and have mutual effects on each other. According to the findings from this study, their good levels of intercultural sensitivity help individuals to initiate intercultural communication and their intercultural communication competence helps them to perform effective interactions. The results from this study may help and encourage researchers and individuals to focus on these two important attributes of intercultural communication.